(untitled) (Homoeopathy for All, 2022)
right hand portion of the abdominal cavity, beneath the diaphragm, and on top of the stomach, right kidney, and intestines. Weighing about 3 pounds, the liver is reddish-brown in color and feels rubbery to the touch. Normally you can’t feel the liver, because it’s protected by the rib cage. There are 2 distinct sources that supply blood to the liver, including the following:Oxygenated blood flows in from the hepatic artery Nutrient-rich blood flows in from the hepatic portal vein The liver holds about one pint (13%) of the body’s blood supply at any given moment. The liver has two large sections, called the right and the left lobes. The gallbladder sits under the liver, along with parts of the pancreas and intestines. Both are made up of 8 segments that consist of 1,000 lobules (small lobes). These lobules are connected to small ducts (tubes) that connect with larger ducts to form the common hepatic duct. The common hepatic duct transports the bile made by the liver cells to the gallbladder and duodenum (the first part of the small intestine) via the common bile duct.